Survival-associated alternative splicing events interact with the immune microenvironment in stomach adenocarcinoma - Ye, Zai-Sheng; Zheng, Miao; Liu, Qin-Ying; Zeng, Yi; Wei, Sheng-Hong; Wang, Yi; Lin, Zhi-Tao; Shu, Chen; Zheng, Qiu-Hong; Chen, Lu-Chuan (World journal of gastroenterology : WJG, 2021)
Alternative splicing (AS) increases the diversity of mRNA during transcription; it might play a role in alteration of the immune microenvironment, which could influence the development of immunotherapeutic strategies against cancer.BACKGROUNDAlternative splicing (AS) increases the diversity of mRNA during transcription; it might play a role in alteration of the immune microenvironment, which could influence the development of immunotherapeutic strategies against cancer.To obtain the transcriptomic and clinical features and AS events in stomach adenocarcinoma (STAD) from the database. The overall survival data associated with AS events were used to construct a signature prognostic model for STAD.AIMTo obtain the transcriptomic and clinical features and AS events in stomach adenocarcinoma (STAD) from the database. The overall survival data associated with AS events were used to construct a signature prognostic model for STAD.Differentially expressed immune-related genes were identified between subtypes on the basis of the prognostic model. In STAD, 2042 overall-survival-related AS events were significantly enriched in various pathways and influenced several cellular functions. Furthermore, the network of splicing factors and overall-survival-associated AS events indicated potential regulatory mechanisms underlying the AS events in STAD.METHODSDifferentially expressed immune-related genes were identified between subtypes on the basis of the prognostic model. In STAD, 2042 overall-survival-related AS events were significantly enriched in various pathways and influenced several cellular functions. Furthermore, the network of splicing factors and overall-survival-associated AS events indicated potential regulatory mechanisms underlying the AS events in STAD.An eleven-AS-signature prognostic model (CD44|14986|ES, PPHLN1|21214|AT, RASSF4|11351|ES, KIAA1147|82046|AP, PPP2R5D|76200|ES, LOH12CR1|20507|ES, CDKN3|27569|AP, UBA52|48486|AD, CADPS|65499|AT, SRSF7| 53276|RI, and WEE1|14328|AP) was constructed and significantly related to STAD overall survival, immune cells, and cancer-related pathways. The differentially expressed immune-related genes between the high- and low-risk score groups were significantly enriched in cancer-related pathways.RESULTSAn eleven-AS-signature prognostic model (CD44|14986|ES, PPHLN1|21214|AT, RASSF4|11351|ES, KIAA1147|82046|AP, PPP2R5D|76200|ES, LOH12CR1|20507|ES, CDKN3|27569|AP, UBA52|48486|AD, CADPS|65499|AT, SRSF7| 53276|RI, and WEE1|14328|AP) was constructed and significantly related to STAD overall survival, immune cells, and cancer-related pathways. The differentially expressed immune-related genes between the high- and low-risk score groups were significantly enriched in cancer-related pathways.This study provided an AS-related prognostic model, potential mechanisms for AS, and alterations in the immune microenvironment (immune cells, genes, and pathways) for future research in STAD.CONCLUSIONThis study provided an AS-related prognostic model, potential mechanisms for AS, and alterations in the immune microenvironment (immune cells, genes, and pathways) for future research in STAD.